2005
DOI: 10.1158/1055-9965.epi-05-0027
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Cancer Development

Abstract: There is epidemiologic evidence that the hydrophilic 3-hydroxy-3-methylglutaryl CoA (HMG-CoA) reductase inhibitor pravastatin increases the incidence of some extrahepatic cancers, although this finding has been attributed to chance. We hypothesize that pravastatin is able to promote the development of cancer by causing an induction of HMG-CoA reductase and, hence, mevalonate synthesis in extrahepatic tissues. We have shown that mevalonate, the product of HMG-CoA reductase, promotes the growth of breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
69
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 24 publications
2
69
0
Order By: Relevance
“…Our results on type of statin also support evolving evidence that hydrophobic statins have antiproliferative effects on certain cancer cells [39][40][41]. It has been suggested that hydrophilic statins promote cancer [39], but our results suggest an inverse association between hydrophilic statin use and prostate cancer risk.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results on type of statin also support evolving evidence that hydrophobic statins have antiproliferative effects on certain cancer cells [39][40][41]. It has been suggested that hydrophilic statins promote cancer [39], but our results suggest an inverse association between hydrophilic statin use and prostate cancer risk.…”
Section: Discussionsupporting
confidence: 88%
“…To make conclusions about the effect of statins on prostate cancer prevention, mechanistic data suggests that the type, dose, and potency of statin used and the serum concentrations achieved need to be considered in observational studies [39,43]. We agree with Platz that the promising and consistent findings from the most recently published studies are remarkable [44], but many of the specifics on statin use (e.g., individual statins, potency) have not been adequately addressed, and the influence of detection bias [44] as well as other confounders such as socioeconomic status need further study.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have hypothesized hydrophobic statins to have antiproliferative effects on breast cancer cells (31,32) and hydrophilic statins to promote cancer (33). We were unable to evaluate hydrophilic statin use due to the small number of hydrophilic only statin users in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hydrophilic statins have no inhibitory effect on HMG-CoA reductase activity in cells with an extrahepatic origin, while statins are involved in mevalonic acid synthesis and could potentially increase carcinogenic risk (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%